Two Concepts of Mental Health: Rationality versus Assertiveness - Vargo, James; Braun, Peter H. (Canadian Journal of Counselling and Psychotherapy, 2012)
Two concepts of some importance to mental health arerationality and assertiveness. Both of these are implicit in the therapeuticapproaches of two major schools of counselling. This study attempted todiscover which of the two concepts is more central to good mental health.For this purpose, measures of both rationality and assertiveness wereobtained from two samples: (1) a random sample of non-institutionalized(normal) subjects, and (2) a sample of psychiatric inpatients. Resultsindicate that there was a proportionately greater shift toward irrationalityfrom the normal to the inpatient sample than there was towardlack of assertiveness (p less than .00001). Hence, it was concluded thatrationality is a more central concept to good mental health than assertiveness.However, these results are not to be interpreted as beingindicative of the relative merits of the above mentioned schools of therapybecause the degree to which the instruments used here measure theaspired goal states of these therapeutic approaches is unknown. Moreresearch is needed before such conclusions are warranted1.